2005
DOI: 10.1063/1.1871334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal annealing on deep-level defects and minority-carrier electron diffusion length in Be-doped InGaAsN

Abstract: We report the effects of ex situ thermal annealing on the deep-level defects and the minority-carrier electron diffusion length in Be-doped, p-type In0.03Ga0.97As0.99N0.01 grown by solid source molecular-beam epitaxy. Deep-level transient spectroscopy measurements reveal two majority-carrier hole traps, HT1 (0.18 eV) and HT4 (0.59 eV), and two minority-carrier electron traps, ET1 (0.09 eV) and ET3 (0.41 eV), in the as-grown sample. For the sample with postgrowth thermal annealing, the overall deep-level defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
5
19
0
Order By: Relevance
“…They also found that deep levels may appear after annealing at about 700 o C. Since our samples are also annealed at 700 o C, appearance of the traps is not surprising after the thermal annealing. The observed energy level with 0.1eV activation energy is also observed by Xie et al using DLTS technique [9] and ascribed for an electron trap level.…”
Section: Contributed Articlesupporting
confidence: 71%
See 1 more Smart Citation
“…They also found that deep levels may appear after annealing at about 700 o C. Since our samples are also annealed at 700 o C, appearance of the traps is not surprising after the thermal annealing. The observed energy level with 0.1eV activation energy is also observed by Xie et al using DLTS technique [9] and ascribed for an electron trap level.…”
Section: Contributed Articlesupporting
confidence: 71%
“…Of the observed trap levels, the traps having the 0.16 eV, 0.18 eV, and 0.3 eV activation energies have already been observed in GaInNAs/GaAs system using similar techniques [5,9,10] Contributed Article [11,12]. They also found that deep levels may appear after annealing at about 700 o C. Since our samples are also annealed at 700 o C, appearance of the traps is not surprising after the thermal annealing.…”
Section: Contributed Articlesupporting
confidence: 61%
“…However, this effort had initially suffered from the difficulty in growing high quality, smooth surface morphology and thick (41 mm) 1-1.3 eV nitride materials, namely the Ga 1Ày In y N x As 1Àx layer with y=3x [7]. Success was also limited by the short minority carrier lifetime in bulk GaInNAs materials due to the presence of deep level traps [8]. In order to avoid the detrimental effect of In-N clustering and to embrace the beneficial effect of Sb in possibly reducing N migration, and hence suppressing the formation of N-complex, the GaNAsSb material was investigated [8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…Success was also limited by the short minority carrier lifetime in bulk GaInNAs materials due to the presence of deep level traps [8]. In order to avoid the detrimental effect of In-N clustering and to embrace the beneficial effect of Sb in possibly reducing N migration, and hence suppressing the formation of N-complex, the GaNAsSb material was investigated [8][9][10][11]. To the best of our knowledge, this is the first nitrogenplasma-assisted molecular beam epitaxy (MBE) growth demonstration of GaNAsSb on the Ge/graded-SiGe/Si substrate.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, various schemes, involving the use of $1.0-1.25 eV GaInNAs subcells, have been devised to enhance the efficiency of existing triple and quadruple junction solar cells [2]. Nevertheless, thus far, poor minority carrier properties [3,4] and doping issues [5,6] associated with thick bulk-like dilute nitrides have hindered the success of these approaches [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%